DUAL ROLE OF CATHEPSIN D: LIGAND AND PROTEASE - Fusek, Martin; Vetvicka, Vaclav (Biomedical papers, 2005)
Cathepsin D is peptidase belonging to the family of aspartic peptidases. Its mostly described function is intracellular catabolism in lysosomal compartments, other physiological effect include hormone and antigen processing. For almost two decades, there have been an increasing number of data describing additional roles imparted by cathepsin D and its pro-enzyme, resulting in cathepsin D being a specific biomarker of some diseases. These roles in pathological conditions, namely elevated levels in certain tumor tissues, seem to be connected to another, yet not fully understood functionality. However, despite numerous studies, the mechanisms of cathepsin D and its precursor's actions are still not completely understood. From results discussed in this article it might be concluded that cathepsin D in its zymogen status has additional function, which is rather dependent on a "ligand-like" function then on proteolytic activity.
Keywords: Cathepsin D/Procathepsin D/Cancer/Activation peptide/Mitogenic activity/Proliferation